Design and Optimization of Mixed Flow Pump Impeller Blades – A Review. (2018) - Dash, Nehal; Kumar Roy, Apurba; Kumar, Kaushik
Abstract: Since a number of designing parameters are involved in designing the blades of mixed flow pump, it has always been a tedious and difficult task to design the blades for a mixed flow pump impeller. It requires fundamentals of turbo machinery and fluid mechanics as prerequisites for proceeding further into the designing methodology. Variation of these parameters gives rise to a number of designing options. Also there are many methods available for the designing of mixed flow pump impeller blades like mean stream method, pseudo stream method, singularity method by using fundamentals of fourier transformation, free vortex theory etc. All these methods listed above have their own advantages and disadvantages in designing methodology.